Green energy management in internet of things based on quality of service composition - Chong GUO; Wenqing YAN; Bin XU (Dianxin kexue)
With the rapid development of internet of things technology,the energy consumption of service composition in the internet of things is a key issue to be studied.The service composition problem in the internet of things mostly focuses on the evaluation based on quality of service(QoS) at present and ignores the overall enerqy cornsumption during the dynamic deployment of service qrnposition.Therefore,a QoS evaluation model and an energy evaluation model was proposed for service composition in the internet of things.Finally,considering the service composition in the internet of things is NP hard,the moth-flame optimization (MFO) was successfully applied to the QoS evaluation model and the energy evaluation model.The experimental results show that MFO has a better optimization effect in the above model,so as to realize the green energy management of the quality of service composition in the environment of the internet of things.